Welfare Economics and Rationing - Reder, M. W. (Quarterly Journal of Economics, 1942)
Journal Article Welfare Economics and Rationing Get access M. W. Reder M. W. Reder New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 57, Issue 1, November 1942, Pages 153–159, https://doi.org/10.2307/1881818 Published: 01 November 1942